The Performance Improvement and the Competitiveness of Private Universities (PTS) in North Sumatera through the Strategy of Building Institutional Competence - Muhammad Yamin Siregar; Parulian Sihombing (Budapest International Research and Critics University, 2021)
According to data released by DIKTI 2015 concerning the classification and ranking of the best 200 of higher education in Indonesia is only 5 universities from North Sumatera that are included in the list, both public and private universities. The purpose in this study is to examine whether there in an effect of learning orientation, internal environment and reputation on institutional competence. As well as to test whether there is an effect of competence on the achievement of institutional performance. The unit of analysis in this research is private universities. Respondents of this research were divided into 2 stages: Stage 1 is focused on the leadership of PTS (rector, vice chancellor I, II, or III; director, deputy director I, II, or III; chairman or vice chairman I, II, or III), where one PTS will be represented by one respondent. This study will describe the perceptions of PTS leader regarding organisational learning, the influence of internal environment, reputation, competence strategies and PTS performance. The second stage of respondent was extended to student suppliers, companies using graduate students, students, lectures, administration staff to describe the perception of the institutional competitiveness. The population in this study were all private universities in North Sumatera amounting 267 universities. This study uses 16 indicator so that the minimum sample requirement is 80. The data was collected using questionnaire, while data measured by Likert scale. Data were analysed use Structural Equation Modelling (SEM) through Analysis of Moment Structure (AMOS) version 16.0 program.